The biological basis of smoltification in Atlantic salmon - Morera, Francisco J.; Castro-Guarda, Marcos; Nualart, Daniela; Espinosa, Gabriel; Muñoz, Jose L.; Vargas-Chacoff, Luis (Austral Journal of Veterinary Sciences, 2021)
Chile is the second-largest producer of Atlantic salmon in the world, and the Chilean salmon production accounts for 27% of the world’s production. One important step of the productive cycle in freshwater is the smoltification process that prepares the fish for the marine life stage. This review describes the biological basis of smoltification in Atlantic salmon, with particular attention on branchial osmoregulatory adaptations. We also discuss some of the infectious diseases and problems in smoltification (two of the main causes of losses in Chilean aquaculture) that could be related from a physiological point of view.